Systemic inflammation and cardiovascular risk factors predict rapid progression of atherosclerosis in rheumatoid arthritis - del Rincón, Inmaculada (Ann Rheum Dis, 2014)
OBJECTIVE: To estimate atherosclerosis progression and identify influencing factors in rheumatoid arthritis (RA). METHODS: We used carotid ultrasound to measure intima-media thickness (IMT) in RA patients, and ascertained cardiovascular (CV) risk factors, inflammation markers and medications. A second ultrasound was performed approximately 3 years later. We calculated the progression rate by subtracting the baseline from the follow-up IMT, divided by the time between the two scans. We used logistic regression to identify baseline factors predictive of rapid progression. We tested for interactions of erythrocyte sedimentation rate (ESR) with CV risk factors and medication use. RESULTS: Results were available for 487 RA patients. The mean (SD) common carotid IMT at baseline was 0.571 mm (0.151). After a mean of 2.8 years, the IMT increased by 0.050 mm (0.055), p≤0.001, a progression rate of 0.018 mm/year (95% CI 0.016 to 0.020). Baseline factors associated with rapid progression included the number of CV risk factors (OR 1.27 per risk factor, 95% CI 1.01 to 1.61), and the ESR (OR 1.12 per 10 mm/h, 95% CI 1.02 to 1.23). The ESR×CV risk factor and ESR×medication product terms were significant, suggesting these variables modify the association between the ESR and IMT progression. CONCLUSIONS: Systemic inflammation and CV risk factors were associated with rapid IMT progression. CV risk factors may modify the role of systemic inflammation in determining IMT progression over time. Methotrexate and antitumour necrosis factor agents may influence IMT progression by reducing the effect of the systemic inflammation on the IMT.